Improving the Performance of the Winduhaji Household Industry by Utilizing Android-Based Accounting Applications - Puspasari, Oktaviani Rita; Teguh, Iman; Indrawan, Rizki (MOVE: Journal of Community Service and Engagement, 2025)
Many SME’s industry still experience difficulties in developing their businesses. The main problem is the difficulty of accessing capital to formal financial institutions, due to the lack of implementation of standard financial administration. This community service activity was carried out to help the needs of household industry owners, especially in the Winduhaji area, with 25 participants, using socialization, training and workshop methods as well as mentoring and evaluation. This activity was categorized as successful. This can be seen from the enthusiasm and activeness of the participants at each stage of the activities carried out. The feedback given was very positive, this application was conveyed as very helpful in increasing time efficiency and reducing errors in recording transactions. In addition, they also feel more professional in running a business because they have neater records. Participants also suggested further training to learn more application features such as more detailed reporting or simple financial analysis, which shows a high interest in continuing to utilize technology in managing their businesses.